Strain Compensation and Trade-Off Design Result in Exciton Emission at 306 nm from AlGaN LEDs at Temperatures up to 368 K - Shih-Ming Huang (MDPI AG, 2021)
In this study, we suppressed the parasitic emission caused by electron overflow found in typical ultraviolet B (UVB) and ultraviolet C (UVC) light-emitting diodes (LEDs). The modulation of the p-layer structure and aluminum composition as well as a trade-off in the structure to ensure strain compensation allowed us to increase the p-AlGaN doping efficiency and hole numbers in the p-neutral region. This approach led to greater matching of the electron and hole numbers in the UVB and UVC emission quantum wells. Our UVB LED (sample A) exhibited clear exciton emission, with its peak near 306 nm, and a band-to-band emission at 303 nm. The relative intensity of the exciton emission of sample A decreased as a result of the thermal energy effect of the temperature increase. Nevertheless, sample A displayed its exciton emission at temperatures of up to 368 K. In contrast, our corresponding UVC LED (sample B) only exhibited a Gaussian peak emission at a wavelength of approximately 272 nm.